Understanding plant–microbe interaction of rice and soybean with two contrasting diazotrophic bacteria through comparative transcriptome analysis - Saini, Manish Ranjan; Chandran, Latha P.; Barbadikar, Kalyani Makarand; Sevanthi, Amitha Mithra V.; Chawla, Gautam; Kaushik, Megha; Mulani, Ekta; Phule, Amol Sarjerao; Govindannagari, Rajani; Sonth, Bandeppa; Sinha, Subodh Kumar; Sundaram, Raman Meenakshi; et al. (Frontiers in Plant Science, 2022)
Understanding the beneficial plant-microbe interactions is becoming extremely critical for deploying the microbes in imparting plant fitness and achieving sustainability in agriculture. Diazotrophic bacteria have the unique ability to survive without external sources of nitrogen and simultaneously promote host plant growth but the mechanisms of endophytic interaction in cereals and legumes have not been studied extensively. We have studied the early interaction of two diazotrophic bacteria Gluconacetobacter diazotrophicus (GAB) and Bradyrhizobium japonicum (BRH) in fifteen days old seedlings of rice and soybean up to 120 hours after inoculation (hai) under low nitrogen medium. Root colonization of GAB in rice was higher than BRH and BRH colonization was higher in soybean roots as observed from the scanning electron microscopy at 120 hai. Peroxidase enzyme was significantly higher at 24 hai but thereafter got reduced sharply in soybean and gradually in rice. The roots of rice and soybean inoculated with GAB and BRH harvested from five-time points were pooled and transcriptome analysis was executed along with control. Two pathways, 'Plant pathogen interaction' and 'MAPK signaling', were specific to RG whereas the pathway related to the nitrogen metabolism and plant hormone signaling was specific to RB in rice. Comparative transcriptome analysis of the root tissues revealed several plant-diazotroph-specific differentially expressed genes (DEGs) and metabolic pathways, of plant-diazotroph-specific transcripts viz. chitinase, brassinosteroid, auxin, MYB, nodulin, and NRT were common in all plant-diazotroph combinations; three transcripts viz. NAR, thaumatin, and thionin were exclusive in rice and another three transcripts viz. NAC, ABA and ammonium transporter were exclusive in soybean. Differential expression of these transcripts and reduction in pathogenesis-related (PR) protein expression shows the early interaction. Based on the interaction, it can be inferred that the compatibility of rice and soybean is more with GAB and BRH respectively. We propose that rice is unable to identify the diazotroph as a beneficial microorganism or a pathogen from an early response. So, it expressed the hypersensitivity-related transcripts along with PR proteins. The molecular mechanism of diazotrophic associations of GAB and BRH with rice vis-à-vis soybean will shed light on the basic understanding of host responses to beneficial microorganisms.